Protective role of R381Q (rs11209026) polymorphism in IL-23R gene in immune-mediated diseases: A comprehensive review. (3rd May 2016) - Abdollahi, Elham; Tavasolian, Fataneh; Momtazi-Borojeni, Amir Abbas; Samadi, Morteza; Rafatpanah, Houshang
Abstract: Interleukin-23 (IL-23) is a regulator of cellular immune responses involved in controlling infection and autoimmune diseases. Strong evidence has shown that IL-23 plays a role in the maintenance of immune responses by influencing the proliferation and survival of IL-17-producing T-helper (TH )-17 cells. The critical role of the IL-23/TH 17 axis in immune-mediated diseases has emerged from different studies. It has also been seen that polymorphisms in the IL-23 receptor (IL-23R) gene might influence IL-23 responses. Interestingly, a functional single nucleotide polymorphism (SNP) in the IL-23 receptor gene (IL-23R; rs11209026, 1142 G wild-type A reduced function, Arg381Gln, R381Q) seems to confer a measure of protection against development of inflammatory bowel disease (IBD; Crohn's disease, ulcerative colitis), ankylosing spondylitis, rheumatoid arthritis, psoriasis, thyroiditis, recurrent spontaneous abortion and asthma, suggesting that a perturbation in the IL-23 signaling pathway is likely to be relevant to the pathophysiology of these diseases. The aim of this review was to provide an evaluation of what is currently known about the protective role of R381Q variant in IL-23R gene in immune-based diseases.